The Efficacy of Community Participation Towards Land Use Planning in South African Local Municipalities - Masenya, Malesela Jim; Kgobe, France Khutso Lavhelani (Brawijaya University, 2023)
The aim of the paper to examine the efficacy of community participation in land use planning and logically conceptualize it. Participation in the society is understood to be the advantage of a group of citizens to engage in matters that express their eventual growth. As a policy to increase community participation at the community level, the current democratic government has implemented comprehensive municipal planning. For the municipality, land use planning has many significances, especially in resolving human settlement debacles, fostering citizen engagement to decide needs and goals, and addressing the historical spatial inequality brought on by apartheid spatial planning. The execution of land use planning, however, has faced several obstacles, including weak cooperation in areas under the jurisdiction of conventional authorities, unlawful land possession and political intervention, among others. The study argues that if land use planning in South Africa can be well integrated and coordinated the spatial justice can be reached and imbalances of the past can be redressed efficaciously. Nonetheless, the study concludes that communities are also upset with their extent of engagement. Despite the many municipalities general success in achieving citizen engagement, there is already an incomplete backlog in civic interaction owing to unethical activities, budget constraints, lack of capacity and improper targeting.